Strategy for Improving the Quality of Islamic Religious Education Study Programs with Total Quality Management - Deni Zam Jami; Asep Muharam (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2022)
This article aims to find a strategy to improve the quality of the Islamic Religious Education Study Program with Total Quality Management at Islamic Religious Colleges. The method used in this article is qualitative descriptive by describing the existing phenomena. The results showed that the strategy for implementing Total Quality Management in the Islamic Religious Education Study Program, University of Muhammadiyah Malang, began with improving the learning program, providing an Education Laboratory, Arabic and English laboratory, both manual and digital libraries, revamping and repairing ideal infrastructure and facilities, learning facilities. complete, innovative, creative, and fun learning methods, training for lecturers and students, as well as distribution of graduates through the job market. Improvements were made based on data from a questionnaire to students. The strategy for improving the quality of the Islamic Religious Education Study Program with Total Quality Management is for the leaders of the University of Muhammadiyah Malang who are quality-oriented, both input, process, and output by relying on cooperation, stakeholders, both staff and staff lecturers, human resource development, strengthening the body. Quality assurance, implementation of the internal quality audit cycle, management review in Management Review Meetings, formulation and updating of strategic plans and operational plans. Thus the Islamic Religious Education Study Program, University of Muhammadiyah Malang has implemented Total Quality Management to improve quality. This can be seen from various achievements and accreditations at regional, national and international levels.